Efeito do betacaroteno sobre o estresse oxidativo e a expressão de conexina 43 cardíaca - Novo, Rosangela [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2013)
BACKGROUND: Intervention studies have shown an increased mortality in patients who received beta-carotene. However, the mechanisms involved in this phenomenon are still unknown. OBJECTIVE: Evaluate the influence of beta-carotene on oxidative stress and the expression of connexin 43 in rat hearts. METHODS: Wistar rats, weighing approximately 100 g, were allocated in two groups: Control Group (n=30), that received the diet routinely used in our laboratory, and Beta-Carotene Group (n = 28), which received beta-carotene (in crystal form, added and mixed to the diet) at a dose of 500 mg of beta-carotene/kg of diet. The animals received the treatment until they reached 200-250g, when they were sacrificed. Samples of blood, liver and heart were collected to perform Western blotting and immunohistochemistry for connexin 43; morphometric studies, dosages of beta-carotene by high-performance liquid chromatography as well as reduced glutathione, oxidized glutathione and lipids hydroperoxides were performed by biochemical analysis. RESULTS: Beta-carotene was detected only in the liver of Beta-Carotene Group animals (288 ± 94.7 µg/kg). Levels of reduced/oxidized glutathione were higher in the liver and heart of Beta-Carotene Group animals (liver - Control Group: 42.60 ± 1.62; liver - Beta-Carotene Group: 57.40 ± 5.90; p = 0.04; heart: - Control Group: 117.40 ± 1.01; heart - Beta-Carotene Group: 121.81 ± 1.32 nmol/mg protein; p = 0.03). The content of total connexin 43 was larger in Beta-Carotene Group. CONCLUSION: Beta-carotene demonstrated a positive effect, characterized by the increase of intercellular communication and improvement of anti-oxidizing defense system. In this model, mechanism does not explain the increased mortality rate observed with the beta-carotene supplementation in clinical studies. (Arq Bras Cardiol. 2013; [online].ahead print, PP.0-0)

FUNDAMENTO: Estudos de intervenção mostraram aumento da mortalidade em pacientes que receberam betacaroteno. Contudo, não são conhecidos os mecanismos envolvidos nesse fenômeno. OBJETIVO: Avaliar a influência do betacaroteno sobre o estresse oxidativo e a expressão de conexina 43 em coração de ratos. MÉTODOS: Ratos Wistar, pesando aproximadamente 100 g, foram alocados em dois grupos: Grupo Controle (n = 30), que recebeu a dieta usada de rotina em nosso laboratório, e Grupo Betacaroteno (n = 28), que recebeu betacaroteno (na forma de cristal, adicionado e misturado à dieta) na dose de 500 mg de betacaroteno/kg de dieta. Os animais receberam tratamento até que atingissem entre 200 e 250 g, quando eram sacrificados. Foram coletados sangue, fígado e coração para realização de Western blotting e imunoistoquímica para conexina 43; foram realizados estudos morfométricos, dosagens de betacaroteno por cromatografia líquida de alta eficiência bem como de glutationa reduzida, glutationa oxidada e hidroperóxidos de lipídeos por análises bioquímicas. RESULTADOS: O betacaroteno foi detectado apenas no fígado dos animais do Grupo Betacaroteno (288 ± 94,7 µg/kg). Os níveis de glutationa reduzida/glutationa oxidada foram maiores no fígado e no coração dos animais do Grupo Betacaroteno (fígado - Grupo Controle: 42,60 ± 1,62; fígado - Grupo Betacaroteno: 57,40 ± 5,90; p = 0,04; coração: - Grupo Controle: 117,40 ± 1,01; coração - Grupo Betacaroteno: 121,81 ± 1,32 nmol/mg proteína; p = 0,03). O conteúdo de conexina 43 total foi maior no Grupo Betacaroteno. CONCLUSÃO: O betacaroteno apresentou efeito benéfico, caracterizado pelo aumento da comunicação intercelular e melhora do sistema de defesa antioxidante. Nesse modelo, os mecanismos não explicam a maior mortalidade observada com a suplementação de betacaroteno em estudos clínicos. (Arq Bras Cardiol. 2013; [online].ahead print, PP.0-0)
Effect of beta-carotene on oxidative stress and expression of cardiac connexin 43
Keywords: Beta Caroteno; Estresse Oxidativo; Ratos; Conexina 43; Remodelação Ventricular; Beta Carotene; Oxidative Stress; Rats; Ventricular Remodeling